Morphine, but not Trauma, Sensitizes to Systemic Acinetobacter baumannii Infection - Breslow, Jessica M. (2011)
Acinetobacter baumannii is an important nosocomial pathogen in civilian intensive care units. Recently the incidence has increased in wounded military personnel. Morphine is documented in numerous animal studies to be immunosuppressive and to sensitize to infection. The hypotheses were tested that morphine, administered for analgesia in the battlefield, predisposes to Acinetobacter infection, and that the opioid may have an additive or synergistic effect with trauma. To test these hypotheses, an intraperitoneal infection model was established in mice using several Acinetobacter strains. Morphine administered for 48 hr by implantation of a slow-release morphine pellet increased mortality compared to animals receiving a placebo pellet, an effect that was blocked by the mu-opioid receptor antagonist, naltrexone. Acinetobacter burdens in the blood, spleens, livers, and lungs of morphine-treated mice, were significantly higher than those in placebo-treated animals, confirming that mortality was due to potentiated growth of the bacteria. There were also elevated levels of pro-inflammatory cytokines in morphine-treated versus placebo-treated mice. Morphine caused a reduction in the total number of cells in the peritoneal cavity, a decrease in the percentage and total numbers of neutrophils, and a decrease in the total number of macrophages. Morphine treatment also suppressed levels of the neutrophil-inducing molecules, IL-17A and KC/CXCL1. However, IL-17A(−/−) mice given morphine were not sensitized to Acintobacter infection to a greater degree than similarly treated wild-type mice. Trauma alone did not sensitize to Acinetobacter infection, and there was no additive effect between morphine and trauma. These results support the hypothesis that morphine potentiates Acinetobacter infection.